Maximising business returns to corporate social responsibility communication: An empirical test. (27th March 2019) - Pérez, Andrea; del Mar García de los Salmones, María; Liu, Matthew Tingchi
Abstract: Based on a classic conceptual model of corporate social responsibility (CSR) communication, we developed an empirical research study to test how several aspects of CSR message content (i.e., issue importance, impact, motives, fit, commitment) are associated with external support responses (i.e., purchase, advocacy). We also tested the moderating role of stakeholder‐ and company‐specific factors (i.e., issue support and industry, respectively) in the proposed model. Data were collected from 302 participants who evaluated the same CSR information displayed in the websites of a fictitious bank and a fictitious restaurant chain. The findings suggest that better perceptions on how the CSR message reinforces issue importance, corporate CSR impact and altruistic motives lead to higher purchase and advocacy intentions. CSR fit is related only to advocacy, while CSR commitment does not have any significant impact on participants' responses. Some new interdependence relationships are also identified among issue importance, motives, fit, and commitment. The moderating role of issue support and industry is confirmed.